High open-circuit voltages in lead-halide perovskite solar cells: experiment, theory and open questions. (8th July 2019) - Kirchartz, Thomas
Abstract : One of the most significant features of lead-halide perovskites is their ability to have comparably slow recombination despite the fact that these materials are mostly processed from solution at room temperature. The slow recombination allows achieving high open-circuit voltages when the lead-halide perovskite layers are used in solar cells. This perspective discusses the state of the art of our understanding and of experimental data with regard to recombination and open-circuit voltages in lead-halide perovskites. A special focus is put onto open questions that the community has to tackle to design future photovoltaic and optoelectronic devices based on lead-halide perovskites and other semiconductors with similar properties. This article is part of a discussion meeting issue 'Energy materials for a low carbon future'.